2022
DOI: 10.1186/s12885-021-09108-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-scores as prognostic markers of overall survival in lung cancer: a register-based study of 6,210 Danish lung cancer patients

Abstract: Background Inflammation-scores based on general inflammation markers are suggested as prognostic markers of overall survival (OS) in lung cancer. However, whether these inflammation-scores improves the prognostication performed by well-established prognostic markers is unsettled. In a large register-based lung cancer patient cohort, nine different inflammation-scores were compared, and their ability to optimize the prognostication of OS was evaluated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Recently, compound prognostic scores derived from peripheral blood count indices have garnered significant interest as indirect measures of inflammatory pressure in cancer [ 25 , 26 ]. These scores generally involve dividing the counts of pro-inflammatory cells such as neutrophils, platelets, and monocytes to the lymphocytes, the main drivers of anti-cancer immunity in the tumor vicinity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, compound prognostic scores derived from peripheral blood count indices have garnered significant interest as indirect measures of inflammatory pressure in cancer [ 25 , 26 ]. These scores generally involve dividing the counts of pro-inflammatory cells such as neutrophils, platelets, and monocytes to the lymphocytes, the main drivers of anti-cancer immunity in the tumor vicinity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify more parameters for “high-risk” patients the focus of the International Cancer Society was on analysing the carcinoma microenvironment for the most common cancer entities (e.g., breast or lung cancer) [ 10 , 11 ]. The microenvironment consists of an extracellular matrix, immune-inflammatory cells, blood and lymphatic vascular networks.…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting results in the literature regarding the prognostic role of inflammatory indices. In a study conducted by Winther-Larsen et al [27], high NLR, PLR, and MLR were found to be associated with decreased OS, but no correlation was found between HALP score and survival in 5320 stage I-IV non-small cell lung cancer patients. It is thought that the difference in the analyzed patient stages, the effects of oncological treatments, and genetic factors may cause this difference in the literature.…”
Section: Discussionmentioning
confidence: 92%